Self-employment dynamics in rural and urban labour markets - Hannu Tervo (European Regional Science Association (ERSA), 2004)
Only few in-depth studies of the alternation between different labour market states have been published. This paper deals with the alternation between self-employment, paid-employment and non-employment in Finland in 1987-1999, paying special attention to differences in self-employment dynamics between areas characterized by different labour market conditions, viz. rural and urban locations. The analysis is based on a one-percent random sample drawn from panel data on the census and longitudinal employment statistics. The results show differences in the transition processes between the three labour market states by the type of area. The results suggest that alternation between different employment options is likely to increase, if employment opportunities remain low in local labour markets. Five major types of working careers are identified, all of which are more common in rural than urban areas. The type of area is importantly related to alternating working careers even when all the important control variables are included into the models.
Keywords: 330